Medication stewardship in the operating theatre in Malaysia: A quality improvement project - Siti Nadzrah Yunus; Nur Haryanti Izumi Suhaimi; Ka Ting Ng; Ili Syazana Jamal Azmi; Noorjahan Haneem Md Hashim; Ina Ismiarti Shariffuddin (Indian Journal of Anaesthesia)
Background and Aims: A quality improvement project (‘Safe Anaesthesia for ALL-SEAL’) was implemented to reduce preventable medication errors and drug wastage in the operating theatre (OT) of a tertiary hospital. The primary objective of this quality improvement project was to prevent the incidence of medication errors, and the secondary objective was to reduce the wastage of unused drugs. Methods: A pre-intervention questionnaire and an audit survey were performed, and multidirectional interventions were designed post-survey. A post-intervention survey was conducted to evaluate effectiveness. The incidence of medication errors, including near misses, was assessed for root causes. Unused drugs drawn or diluted in syringes were recorded daily in each OT. The weekly drug orders and mid-week reordering frequency were also monitored. The data were reported as simple means and percentages. Results: Ninety-eight anaesthesia care providers participated in the survey (72.4% doctors and 27.6% anaesthetic nurses). Pre-intervention, 76.1% of respondents had experienced medication errors during their practice. Common errors included misidentification of ampoules or vials (65.2%), miscalculation of dosages (65.2%), improper syringe labelling (56.5%), accidental drug omission (54.3%) and wrong prescriptions (39.1%). The main sources of errors were fatigue/overwork (80.4%) and a hectic OT environment (71.7%). Post-intervention, no incidents of medication errors were reported. In addition, there was a significant reduction in drug wastage. Conclusions: The SEAL project positively prevented medication errors and reduced drug wastage, which should be further validated in other clinical settings.